Risk attitude and belief updating: theory and experiment - Huang, Evelyn Y. H.; Leung, Benson Tsz Kin (Frontiers in Psychology, 2023)
Despite the importance of risk attitude in decision-making, its role in belief updating has been overlooked. Using economic theory, we analyze a dual-self equilibrium where an individual first updates her belief about an uncertain state, then takes an action to maximize her payoff. We show that stronger risk aversion drives more conservative actions, and thus decreases the instrumental value of information relative to the importance of belief-based utility. As a result, the relationship between risk attitude and belief updating depends on the nature of the belief-based utility. With self-relevant information, stronger risk aversion leads to more belief change; whereas with self-irrelevant information, stronger risk aversion leads to less belief change. Our experimental results concur with the theoretical predictions with two settings where subjects update their belief about their IQ and a randomly drawn number, respectively. We discuss implications on persuasion, advertisements, and political campaigns.